2012
DOI: 10.1021/ol3003833
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Reductions for the Regio- and Stereoselective Synthesis of Hydroxy-keto Esters and Dihydroxy Esters

Abstract: Ketoreductases were utilized for the stereoselective synthesis of δ-hydroxy-β-keto esters, β-hydroxy-δ-keto esters, and β,δ-dihydroxy esters. Seven out of eight possible stereoisomers were obtained from the enzymatic reduction of the corresponding β,δ-diketo ester in high enantio- and diastereomeric excess.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Our research group has lengthy experience in biocatalytic reductions of various carbonyl compounds and their applications for the chemoenzymatic synthesis of natural products with biological activity [ 31 , 32 ]. Moreover, we and other research groups have shown that reductive enzymes, like ketoreductases, are valuable and powerful catalysts in the synthesis of optically active intermediates and precursors for many pharmaceuticals [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In the present work, the asymmetric reduction of the keto ester 7 using NADPH-dependent ketoreductases was the key step introducing the chirality of the natural product 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research group has lengthy experience in biocatalytic reductions of various carbonyl compounds and their applications for the chemoenzymatic synthesis of natural products with biological activity [ 31 , 32 ]. Moreover, we and other research groups have shown that reductive enzymes, like ketoreductases, are valuable and powerful catalysts in the synthesis of optically active intermediates and precursors for many pharmaceuticals [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. In the present work, the asymmetric reduction of the keto ester 7 using NADPH-dependent ketoreductases was the key step introducing the chirality of the natural product 1 .…”
Section: Resultsmentioning
confidence: 99%
“…After the clarification of the optimum conditions (phosphate buffer 200 mM, pH 6.9, and temperature 5–8 °C), the stereoselective reduction of 7 was carried out with several ketoreductases to screen and identify the most suitable biocatalyst for the desirable transformation. The enzymes chosen for the screening have displayed high activity in structurally similar carbonyl substrates [ 32 , 36 , 37 ]. The well-established system for the NADPH recycling was applied in all enzymatic reactions ( Scheme 4 ) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current work is focused on the analogous degradation of decane and defining the role of coenzyme B 12 in alkane degradation. The expertise of I. Smonou's group in stereochemically controlled enzymatic reductions of ketones [4] led, in collaboration with Golding's group, to the synthesis of (2R,9S)-decane-2,9-diol, a precursor of (2R,9S)-[2,9-2 H 2 ]decane, required for studies of anaerobic decane oxidation. In related studies, Buckel and Golding (with J. Heider, Marburg) have shown that benzylsuccinate synthase combines toluene and fumarate with inversion of configuration at the methyl group [5].…”
Section: Working Group 1: Radical Enzymesmentioning
confidence: 99%
“…More recently, the asymmetric reduction of 3,5-diketo acid derivatives allowed the efficient introduction of a chiral center on the side chain through careful optimization of the catalytic hydrogenation of the -carbonyl moiety into a -hydroxy group. [5] Divergent approaches based on building the side chain step by step on the aromatic core through an asymmetric aldol [6] or Claisen [7] reaction are also well known. However, advantages in terms of convenience are nullified by low yield and optical purity if applied for the direct connection of a preformed side chain with the statin core.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the chemical or biochemical desymmetrization of 3‐hydroxyglutaric anhydride is the most straightforward method to obtain an optical purity higher than 99 %. More recently, the asymmetric reduction of 3,5‐diketo acid derivatives allowed the efficient introduction of a chiral center on the side chain through careful optimization of the catalytic hydrogenation of the β‐carbonyl moiety into a β‐hydroxy group …”
Section: Introductionmentioning
confidence: 99%